2018
DOI: 10.1523/jneurosci.3240-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Synaptopathy in the Aging Cochlea: Characterizing Early-Neural Deficits in Auditory Temporal Envelope Processing

Abstract: Aging listeners, even in the absence of overt hearing loss measured as changes in hearing thresholds, often experience impairments processing temporally complex sounds such as speech in noise. Recent evidence has shown that normal aging is accompanied by a progressive loss of synapses between inner hair cells and auditory nerve fibers. The role of this cochlear synaptopathy in degraded temporal processing with age is not yet understood. Here, we used population envelope following responses, along with other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
185
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(205 citation statements)
references
References 86 publications
(54 reference statements)
16
185
1
3
Order By: Relevance
“…In humans, recent findings 40 suggest that appreciable auditory nerve fiber loss begins in early adulthood, well before degeneration is 41 noted in cochlear sensory cells or spiral ganglion cell bodies (Wu et al, 2018). In animal models, a loss of 1 cochlear afferent synapses disrupts the encoding of rapid timing cues, without affecting thresholds, 2 consistent with observations made in our subject cohort (Parthasarathy and Kujawa, 2018;Shaheen, 3 Valero and Liberman, 2015). In humans, it is impossible to directly assess the status of cochlear afferent 4 synapses in vivo, though indirect proxies for cochlear afferent innervation may be possible (Liberman et 5 al., 2016;Mehraei et al, 2016;Bharadwaj et al, 2015;Guest et al, 2017;Prendergast et al, 2017a;6 Prendergast et al, 2017b;Grinn et al, 2017;Bramhall et al, 2017).…”
Section: From Mechanisms To Biomarkers For Hidden Hearing Disorder 15supporting
confidence: 82%
See 1 more Smart Citation
“…In humans, recent findings 40 suggest that appreciable auditory nerve fiber loss begins in early adulthood, well before degeneration is 41 noted in cochlear sensory cells or spiral ganglion cell bodies (Wu et al, 2018). In animal models, a loss of 1 cochlear afferent synapses disrupts the encoding of rapid timing cues, without affecting thresholds, 2 consistent with observations made in our subject cohort (Parthasarathy and Kujawa, 2018;Shaheen, 3 Valero and Liberman, 2015). In humans, it is impossible to directly assess the status of cochlear afferent 4 synapses in vivo, though indirect proxies for cochlear afferent innervation may be possible (Liberman et 5 al., 2016;Mehraei et al, 2016;Bharadwaj et al, 2015;Guest et al, 2017;Prendergast et al, 2017a;6 Prendergast et al, 2017b;Grinn et al, 2017;Bramhall et al, 2017).…”
Section: From Mechanisms To Biomarkers For Hidden Hearing Disorder 15supporting
confidence: 82%
“…supplement 2B). We also noted considerable inter-1 subject variability in the amplitude of auditory brainstem response (ABR) wave 1, a marker for peripheral 2 nerve health, which decreases over the course of normal aging or following neuropathic noise exposure 3 (Figure 1H-I) (Parthasarathy and Kujawa, 2018;Fernandez et al, 2015). Both indirect measures of auditory 4 peripheral health showed substantial inter-subject variability despite normal hearing thresholds, but the 5 particular levels were not statistically related to performance on the competing digits task, demonstrating 6 that these markers of peripheral damage do not have a direct contribution to this measure of multi-talker 7 speech performance in our subject population (r = 0.10 p = 0.64, Figure 1J, Fig.…”
Section: Introduction 14mentioning
confidence: 83%
“…This suggests that within the older group, there is a single HP mechanism degrading performance for both noise types. This mechanism might relate to degraded TENV encoding, which recent studies have associated with age-related synaptopathy in rodents (Parthasarathy and Kujawa 2018). In contrast, we observed that LP speech cues were degraded differently depending on the noise type in the same older listener group.…”
Section: Origin Of Speech Recognition Deficitscontrasting
confidence: 60%
“…There are several reports showing that these standard clinical measures are poor predictors of speech recognition in noise (Festen and Plomp 1983;Papakonstantinou, Strelcyk, and Dau 2011), and that suprathreshold hearing deficits targeting temporal fine-structure (TFS) or envelope encoding (TENV) are important for speech intelligibility as well (Lorenzi et al 2006;Hopkins and Moore 2011;Papakonstantinou, Strelcyk, and Dau 2011;Léger, Moore, and Lorenzi 2012a,b). Lastly, there is growing physiological evidence that supra-threshold processing of audible sound might be compromised by synaptopathy (Bharadwaj et al 2014(Bharadwaj et al , 2015Liberman et al 2016;Parthasarathy and Kujawa 2018;Parthasarathy, Herrmann, and Bartlett 2018) as a consequence of aging.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, unlike the typical human EFR experiments where modulation rates are lower (see Shinn-Cunningham et al, 2017 for a review), high-modulation rate EFRs are an alternate measure of nerve integrity much like the ABR wave I and may benefit from similar normalization procedures. For instance, Parthasarathy & Kujawa (2018) suggested that the high AM-rate EFRs that hypothetically originate from the nerve could be normalized by lower rate EFRs which may originate from the post-synaptic currents in midbrain neurons driven by input afferents; this is analogous to the wave I -wave V ratio.…”
Section: Auditory Brainstem Response (Abr) Wave I Amplitudementioning
confidence: 99%